Reaction of ichthyofauna in the amazon region to different sound impulses - Maroja, Armando de Mendonça; Silva, Tania Machado da; Garavelli, Sérgio Luiz; Zara, Luiz Fabrício (Seven Editora, 2023)
This work is part of a research and development project (R&D - 06631-0009/2019), which aims to develop and validate technological strategies integrating physicochemical systems for the repulsion of the ichthyofauna from the suction pipe during the shutdown of the generating units of the Jirau Hydroelectric Power Plant, located on the Madeira River, state of Rondônia, Brazil. One of the strategies is the acoustic barrier, which is being developed to meet the particularities of the Amazonian fish species in the study area. The barrier will prevent and/or minimize fish entering the suction pipes during turbine stops and restarts. In the first stage, acoustic parameters were identified: auditory threshold and hearing frequency range of the most common fish caught at the plant. In the second stage, computer simulations were carried out that defined the configuration and power of the sound source required for the barrier. In the third stage, the characterization of aerial and underwater sounds in the vicinity of the plant was carried out. In this stage, in situ tests were carried out using the simulated arrangement with the sound source of the Lubell LL916 and the C75 hydrophone of Cetacean Research, testing the efficiency of 4 different noise configurations: pink, thunder, shooting and with well-defined tonal components. The tests were carried out at the spillway of the Jirau Hydroelectric Power Plant, where the movement of fish was monitored before and during the activation of the sound source. The results indicated that all the different types of sounds have the potential to increase the movement of the fish, but with different performances. Sound generated with tonal components increased movement by 57 percent, thunder noise by 43 percent, gunshot noise by 37 percent, and pink noise by 29 percent. These results are promising and will be applied in tests on suction tubes in the next stage of the study. DOI:https://doi.org/10.56238/sevened2023.006-075